1985
DOI: 10.1002/art.1780280515
|View full text |Cite
|
Sign up to set email alerts
|

Role of synovial membrane inflammation in cartilage matrix breakdown in the Pond‐Nuki dog model of osteoarthritis

Abstract: Using the Pond-Nuki procedure, osteoarthritis was induced in 26 crossbred dogs. Their right knees were subjected to anterior cruciate ligament sectioning, and their left knees received a sham operation. The unoperated knees of 7 additional dogs served as controls. Cartilage and synovial membranes were excised 2, 4, and 8 weeks after surgery. Collagenolytic activity, determined by direct tissue assay, was higher at all times tested in osteoarthritic cartilage and synovia than in sham operated and control specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…Synovium samples (3 infrapatellar samples per joint) were fixed in 4% formaldehyde, embedded in paraffin, and sectioned into 3-m slices. Synovial inflammation was quantified on hematoxylin and eosin-stained tissue sections using the Goldenberg-Cohen score as modified by Pelletier (synovial lining cell hyperplasia, villous hyperplasia, and cell influx) (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…Synovium samples (3 infrapatellar samples per joint) were fixed in 4% formaldehyde, embedded in paraffin, and sectioned into 3-m slices. Synovial inflammation was quantified on hematoxylin and eosin-stained tissue sections using the Goldenberg-Cohen score as modified by Pelletier (synovial lining cell hyperplasia, villous hyperplasia, and cell influx) (49,50).…”
Section: Methodsmentioning
confidence: 99%
“…The animals were randomly divided into 5 experimental groups: 7 dogs were operated and left untreated (untreated OA group); 6 were operated and treated with omeprazole (20 mg/day orally; Astra Pharma, Mississauga, Ontario, Canada); 6 were operated and treated with diclofenac (0.25 mglkg twice daily orally; Sigma, St. Louis, MO) plus omeprazole (20 mg/day orally); 6 were operated and treated with tenidap (3 mg/kg twice daily orally; Pfizer Central Research, Groton, CT) plus omeprazole (20 mg/day orally); 8 were not operated (normal controls). Omeprazole was given to drug-treated dogs because of their gastrointestinal sensitivity to antirheumatic drugs; omeprazole proved to fully protect the animals against drug-related gastrointestinal side effects that had been encountered during preliminary studies.…”
Section: Methodsmentioning
confidence: 99%
“…Cartilage lesions are probably related to mechanical as well as biochemical factors, including the enzymatic cleavage of matrix macromolecules (4). Matrix metalloproteases (MMP), such as collagenase and stromelysin, have been found to be significantly increased in OA cartilage and synovial membrane, in humans as well as in the experimental dog model (4)(5)(6). It is becoming more and more evident that MMP play an important role in cartilage destruction.…”
mentioning
confidence: 99%
“…Many laboratories, includ-ing our own, have shown that the Pond-Nuki dog model of OA, produced by sectioning the anterior cruciate ligament of the knee (l6), induces histologic and biochemical changes similar to those in human OA (7,17,18). These include increased levels of proteolytic enzymes in OA cartilage (2,6,7) and synovial inflammation (19). We have previously demonstrated with this model that corticosteroids can suppress the in vivo increase in metalloproteases (6,19).…”
Section: Protective Effects O F Corticosteroids On Cartilage Lesions mentioning
confidence: 98%